AUTOMATIC MANUAL SMART LIGHT CONTROL SYSTEM WITH STATUS FEEDBACK - Samuel Beta; Fahmi Baihaqi; Ivandi Julatha (Politeknik Negeri Semarang, 2023)
The need for light is one of the main needs for human life today. Advances in technology are very helpful in many aspects of life, especially in terms of light. Thanks to advances in technology, humans do not only rely on sunlight as a means of lighting their daily lives because lamps have been found as a substitute for lighting. Controlling the lights manually certainly has drawbacks as is often the case in this village where the owner often leaves the house with the lights on, this can cause a waste of electricity and short circuits can occur in the lights if they are constantly on. Where researchers use applied research methods which are research methods that are carried out with the intention of implementing, testing, and evaluating the ability of a theory that is applied in solving practical problems. However, researchers also use IoT (Internet of Things) technology and Internet Messenging applications, namely Telegram. Where this IoT technology is a technology that utilizes the internet network connected to a network of lights through a sensor, namely the NodeMCU Esp8266 Microcontroller. While the Telegram application is used as an aid to make it easier to monitor or control both turning on and off the lights remotely using the application, the Telegram application also sends feedback on the status of the lights. From the results of this study, it can be expected that this control system can assist in controlling or controlling lights easily and practically over long distances using the telegram application..